Robust K nearest neighbor query processing algorithm in wireless sensor networks - LIU Liang; QIN Xiao-lin; LIU Ya-li; LI Bo-han (Tongxin xuebao)
A robust K nearest neighbor query processing algorithm called ROC-KNN was proposed.It divides the query region into several sub-regions according the network topology.Each sub-region has a cluster node which collects the sensory data in it,sends it to the cluster node in the next sub-region until traversing all the sub-regions.Two distributed heuristic sub-region size setting and cluster node election algorithms were proposed to reduce the energy consumption.A query processing recovery algorithm using the non-cluster nodes in each sub-region was designed to reduce the outage probability caused by cluster node failures.The experimental results show that the ROC-KNN outperforms the existing algorithms in terms of energy consumption and query success rate.